Predicting green product purchase: Applying a Cognitive-Affective-Behavior hierarchy - Michael Rusiviro Jacob; Yizzy Weny Putri; Sabrina Oktaria Sihombing (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2020)
There are three major elements that considered being the expected certainty in green product purchasing is environmental attitude, product attitude, and also purchasing intention. Other variables such as collectivism, individualism, subjective and objective knowledge, environmental awareness, government’s role, media exposure, social influence, and perceived monetary value are linked to these factors as well. This research aims to examine regarding Indonesian consumers’ in creating green product purchase intention by applying Cognitive-Affective-Behavior hierarchy This study used convenience sampling as the design of the sampling with 262 respondents as the sample size. Questionnaires were distributed by spreading through internet and social media. After the data of all respondents were collected, then the analysis process of the data is conducted by using SEM PLS. However, there were seven hypotheses that showed unsupported results. These hypotheses are relationship between collectivism and environmental attitude, individualism and environmental attitude, individualism and product attitude, objective knowledge and environmental attitude, the role of government and product attitude, media exposure and environmental attitude, environmental attitude and purchase intention.